ABNORMALITY NOTIFYING METHOD AND MAINTENANCE METHOD - OKUMURA HIRONOBU (2005)
PROBLEM TO BE SOLVED: To easily know a degree of deterioration to abnormality, to accurately grasp a situation, to perform necessary maintenance and to reduce unnecessary maintenance. SOLUTION: This abnormality informing method includes a process for detecting a status value relating to a factor of abnormality, a process for integrating an operation time of an apparatus in a state that the detected status value is less than a reference value, and a process for informing the information on the degree of deterioration to abnormality on the basis of the operation time of the apparatus integrated in the integrating process. This maintenance method includes a process for detecting the status value relating to the factor of abnormality, a process for integrating the operation time of the apparatus in a state that the detected status value is less than a reference value, and a process for informing the information on the degree of deterioration to the abnormality on the basis of the operation time of the apparatus integrated in the integrating process, and the maintenances of the apparatus and/or its peripheral devices are performed on the basis of the information on the degree of deterioration. COPYRIGHT: (C)2005,JPO&NCIPI